2017
DOI: 10.1080/09688080.2017.1329607
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to explore the barriers and enablers for young people with disabilities to access sexual and reproductive health services in Senegal

Abstract: A qualitative study to explore the barriers and enablers for young people with disabilities to access sexual and reproductive health services in Senegal, Reproductive Health Matters, 25:50,[43][44][45][46][47][48][49][50][51][52][53][54]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
84
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 10 publications
17
84
0
3
Order By: Relevance
“…Policy and research have identified the need for persons with learning disability to explore and express their sexuality and to have opportunities to form relationships like the rest of society (Valuing People, ; Valuing People Now, ; Malta National Disability Policy, ; UNCRPD, ). However, at the very roots of society lie socio‐cultural beliefs that influence the lives of persons with learning disability, including their sexual experiences (Burke et al, ). The cultural climate within the context described in this research conveys the restricted experience of social interaction in the lives of persons with learning disability.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Policy and research have identified the need for persons with learning disability to explore and express their sexuality and to have opportunities to form relationships like the rest of society (Valuing People, ; Valuing People Now, ; Malta National Disability Policy, ; UNCRPD, ). However, at the very roots of society lie socio‐cultural beliefs that influence the lives of persons with learning disability, including their sexual experiences (Burke et al, ). The cultural climate within the context described in this research conveys the restricted experience of social interaction in the lives of persons with learning disability.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Furthermore, traditional ways of looking at sexuality in Malta inadvertently carry cultural and religious implications that inhibits discussion about sexual exploration and creates a taboo around the subject (Azzopardi Lane & Callus, ; Debattista, ). In such a cultural context, sex has a tendency to be seen within a framework of marriage and procreation, events persons with learning disability are particularly not expected or encouraged to experience (Azzopardi, ; Burke et al, ), but that however, as seen through these findings, seem to be the pinnacle of the aspirations for some of them. Barriers to sexual expression are further inhibited by parental overprotection, which featured strongly within the patriarchal context the research was conducted in.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…accessing health care (8)(9)(10)(11)(12)(13)(14). These barriers are attributed largely to several weaknesses in the health systems as well as individual factors of people with disabilities.…”
mentioning
confidence: 99%
“…people with disabilities in Low and Middle-Income Countries (LMICs) face substantial barriers in accessing health care (8)(9)(10)(11)(12)(13)(14). These barriers are attributed largely to several weaknesses in the health systems as well as individual factors of people with disabilities.…”
mentioning
confidence: 99%